2021
DOI: 10.3389/fvets.2021.680539
|View full text |Cite
|
Sign up to set email alerts
|

Lineage Differentiation Markers as a Proxy for Embryo Viability in Farm Ungulates

Abstract: Embryonic losses constitute a major burden for reproductive efficiency of farm animals. Pregnancy losses in ungulate species, which include cattle, pigs, sheep and goats, majorly occur during the second week of gestation, when the embryo experiences a series of cell differentiation, proliferation, and migration processes encompassed under the term conceptus elongation. Conceptus elongation takes place following blastocyst hatching and involves a massive proliferation of the extraembryonic membranes trophoblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 148 publications
1
12
0
Order By: Relevance
“…Even though the developmental rates are similar, DHA could increase the percentage of embryos expressing SOX2 and, consequently, the percentage of embryos that would lead to gestation. Failure of epiblast development has been described in vitro and in vivo, and several authors reported that between 23% and 65% of in vitro produced and transferred embryos no longer had an embryonic disc, as reviewed by Ramos-Ibeas et al [37]. In the present study, regardless of the freezing day, 27.4% to 43.3% of the embryos lacked SOX2 cells and therefore epiblast, after thawing and 48h of culture (Table 4).…”
Section: Medium On the Development And Quality Of Bovine In Vitro-pro...supporting
confidence: 65%
“…Even though the developmental rates are similar, DHA could increase the percentage of embryos expressing SOX2 and, consequently, the percentage of embryos that would lead to gestation. Failure of epiblast development has been described in vitro and in vivo, and several authors reported that between 23% and 65% of in vitro produced and transferred embryos no longer had an embryonic disc, as reviewed by Ramos-Ibeas et al [37]. In the present study, regardless of the freezing day, 27.4% to 43.3% of the embryos lacked SOX2 cells and therefore epiblast, after thawing and 48h of culture (Table 4).…”
Section: Medium On the Development And Quality Of Bovine In Vitro-pro...supporting
confidence: 65%
“…In a similar vein, active enhancers in TE demonstrated very little enrichment for CDX2 motifs, despite notable expression in the blastocyst (Fig. 6k) and presence of CDX2 protein 58,60 . Thus, in terms of genome regulation, CDX2 may play a more prevalent role during later stages of bovine blastocyst development.…”
Section: Chromatin Accessibility Precedes Establishment Of Canonical ...mentioning
confidence: 73%
“…6b ). Moreover, OCT4/POU5F1 expression remains widespread in human and bovine blastocysts, but is already restricted to the ICM in mouse 58,60 ( Fig. 6b ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences were not observed at E14, presumably because those embryos lacking an ED had already degenerated. These observations suggest that failures in epiblast development may underlie the intrinsic high embryo mortality reported during this period of development in both humans and ungulates ( Diskin and Morris, 2008 ; Macklon et al, 2002 ; Perez-Gomez et al, 2021 ). N2B27 was the only medium supporting epiblast survival and ED formation in in vitro -cultured sheep embryos.…”
Section: Discussionmentioning
confidence: 93%